The Scope of Justice Dilemma - Elias L. Khalil (20518877) (2025)
What is the determinant of the scope of justice? Should rules of justice that regulate the interactions of the members of my society be extended to cover how such members interact with outsiders, entities that fall outside the boundary of my society? Two major approaches—namely, the deontological/contractarian and the utilitarian—offer their answers. Although their answers differ, they are universal in the sense that they do not draw a boundary between the members of my society and outsiders. As a result, one answer is deficient while the other is non-feasible. The only possible answer is the “Average Principle”. The Average Principle means that the boundary of my society can expand as long as the average wellbeing (GDP/capita) of my society does not decline. However, the Average Principle faces its own problem: the Average Principle is contingent on one’s group membership—i.e., amounting to a parochial answer. That is, the Average Principle cannot be a universal response as the case with the deontological/contractarian and the utilitarian approaches. In effect, this paper finds that the scope of the justice question faces a dilemma. While the deontological/contractarian and the utilitarian approaches involve universal moral principles, one is deficient and the other is non-feasible. While the Average Principle reasoning is non-deficient and feasible, it cannot amount to universal moral principle. This paper finds that the scope of justice dilemma has no solution that is universal. Other Information Published in: Chinese Political Science Review License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1007/s41111-025-00289-z